The benefits of taekwondo training for undergraduate students: A phenomenological study - Petrovic, K. (Societies, 2017)
The purpose of this phenomenological research was to discover whether training in the Korean martial art of Taekwondo may benefit undergraduate (UG) students in handling stress. The goal of this innovative approach to learning and stress management was to allow UG students from across disciplines at a metropolitan university achieve an increased sense of emotional balance, inner peace, and overall well-being in body, mind, and spirit. No such study has been conducted before now. This research was multidisciplinary in its inclusion of insights from the tenets of higher education, human development and psychology, nursing and sociology, as well as the art, philosophy, and sport of Taekwondo. Ten UG student participants were sought for this research study, though a total of eight students agreed to participate. The study was open to all of the UG students at this university. Phenomenology was used to identify themes that emerged regarding student participant’s experience with stress. Consequently, new ideas were established about the ways in which UG students learned to use Taekwondo training to overcome stress, thereby improving upon and maintaining health and well-being in body, mind, and spirit. © 2017 by the author; licensee MDPI, Basel, Switzerland.
13 citations (Crossref) [2023-10-31]
Keywords: Higher education; Holistic health; Human development; Stress; Taekwondo; Undergraduate students; dept.nur